2011
DOI: 10.1002/chem.201101522
|View full text |Cite
|
Sign up to set email alerts
|

A Designed Cavity for Zwitterionic Species: Selective Recognition of Taurine in Aqueous Media

Abstract: International audienceThe perfect host: Hemicryptophane 1 selectively binds taurine neurotransmitters in CD3CN/D2O. Association constants determined by DOSY NMR spectroscopy demonstrate that this recognition is highly selective over other related substrates. DFT calculations emphasize that only weak intermolecular interactions stabilize the host–guest association (see figure)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 46 publications
1
31
0
Order By: Relevance
“…Various hosts have been investigated for ion‐pair recognition, such as uranyl‐salophen compounds, or calixarene‐based, resorcinarene‐based, or pillararene‐based receptors. Studies of hemicryptophanes have revealed that they are also an appealing type of receptor for this purpose . Hemicryptophanes are chiral molecular containers that include a cyclotriveratrylene (CTV) moiety bonded to a C 3 ‐symmetrical organic group using three linkers whose identity and length can be varied .…”
Section: Introductionmentioning
confidence: 99%
“…Various hosts have been investigated for ion‐pair recognition, such as uranyl‐salophen compounds, or calixarene‐based, resorcinarene‐based, or pillararene‐based receptors. Studies of hemicryptophanes have revealed that they are also an appealing type of receptor for this purpose . Hemicryptophanes are chiral molecular containers that include a cyclotriveratrylene (CTV) moiety bonded to a C 3 ‐symmetrical organic group using three linkers whose identity and length can be varied .…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] They were found to be a novel class of efficient supramolecular catalysts, 11,12 ion pair, 13 or zwitterions receptors 14,15 and led to the design of novel molecular mechanical components as propeller or gyroscope. Their syntheses mainly afford racemic mixtures, and their optical resolution is a common and challenging issue in the research of optically pure molecular hosts.…”
Section: Introductionmentioning
confidence: 99%
“…It is also noteworthy that, among the reported zwitterion receptors,7, 911 only a few examples describe the selective complexation of betaines,9, 11 with most of the systems being devoted to the binding of amino acids 7. 10a,c…”
Section: Resultsmentioning
confidence: 99%